CUERPO Y PERCEPCIÓN EN UNA ZONA RURAL DE MÉXICO: ¿UNA PREOCUPACIÓN SOLO DE MUJERES O TAMBIÉN DE HOMBRES? - Ana Gabriela Romero Juárez; Sara Elena Pérez-Gil Romo; Sergio Aaron De la Rosa Cruz (Universidade do Estado do Rio de Janeiro, 2017)
Introduction: This paper is part of food and gender research, in which the body is considered as a social construct. Concerns on the body, body image and food has become a problem, especially for urban women. However, there is little information on what happens with men and women living in rural areas of the country. Objectives: Investigate how women and men in rural areas perceive their bodies, how they would like to look and what they actually know about food. Methodology: In a rural community located in the State of Mexico, 19 men and 30 women were surveyed, measured and weighed.They selected from 9 figures, according to their self-perception and their desired figure. Results: Some sex differences in body perception were found: men perceived themselves thinner than they are in fact, and some women perceived themselves as overweight. Both groups would like to be thinner. More alterations were observed in male self-perceptions. No gender differences were found in relation to traditional knowledge on food, body and health. Conclusion: Aiming at implementing measures for preventing and treating high-risk eating pratices, which are usually associated with body image issues, it is necessary to increase the number of studies on altered body perception of men and women living in rural areas. DOI: 10.12957/demetra.2017.22559